Celiac disease and its histopathology (Journal of Pathology of Nepal, 2017)
Celiac disease is gluten induced enteropathy and is a chronic inflammatory disorder of the small intestine characterized by malabsorption. It is a common immune mediated disorder which is triggered by consumption of wheat (gluten). It occurs in genetically predisposed individuals (carriers of HLA-DQ2 and DQ8 haplotypes). It is characterized by inflammation of the small-intestinal mucosa and myriad gastrointestinal and systemic manifestations. A duodenal biopsy with positive serology is the gold standard for the diagnosis of Celiac disease. As there are changing presentation for Celiac disease, communication of pathologist and gastroenterologists is essential for appropriate interpretation of duodenal biopsy.